2017
DOI: 10.1017/ppr.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Eels, Beavers, and Horses: Human Niche Construction in the European Late Upper Palaeolithic

Abstract: This paper examines interactions between co-occupants of riverine niches in North West

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Notably, beavers might have played a currently underappreciated role in the sustenance and lifeworlds of at least some interglacial Neanderthals (Hérisson et al, 2015;Kindler, personal communication;Müller and Pasda, 2011). Brown et al (2017) have drawn attention to a possible autoecological entanglement of beavers, eels, and horses underpinning mobiliary art-making in some European Late Upper Palaeolithic contexts, and beavers have been considered as potential high-value prey items for some Late Glacial, especially Allerød, foragers in Northern Europe (Baales and Street, 1996;Charles, 1997;Weber et al, 2011). Mills (2022: 391) has pointed out that beavers were likely important agents of driftwood procurement within the extensive catchment of the Terminal Pleistocene Channel system.…”
Section: Beavers In the Early And Mid-holocene Of Northern Europementioning
confidence: 99%
“…Notably, beavers might have played a currently underappreciated role in the sustenance and lifeworlds of at least some interglacial Neanderthals (Hérisson et al, 2015;Kindler, personal communication;Müller and Pasda, 2011). Brown et al (2017) have drawn attention to a possible autoecological entanglement of beavers, eels, and horses underpinning mobiliary art-making in some European Late Upper Palaeolithic contexts, and beavers have been considered as potential high-value prey items for some Late Glacial, especially Allerød, foragers in Northern Europe (Baales and Street, 1996;Charles, 1997;Weber et al, 2011). Mills (2022: 391) has pointed out that beavers were likely important agents of driftwood procurement within the extensive catchment of the Terminal Pleistocene Channel system.…”
Section: Beavers In the Early And Mid-holocene Of Northern Europementioning
confidence: 99%
“…But there is more: the actions of beavers have also long since attracted humans to those very same habitats (Coles 2006). Indeed, Tolksdorf et al (2017) have recently demonstrated the close cohabitation of Late Palaeolithic foragers and beavers in the same habitat, and Brown et al (2017) have further compiled faunal evidence as well as indications Fig. 17.2 A schematic of how a regular phenotype at t becomes an extended phenotype in t + 1 and then transforms into the constructed niche of a new generation of beaver pups at t + 2 born into the phenotypic extension of the previous generation.…”
Section: The Beaver As Ecosystem Engineer and Niche Constructormentioning
confidence: 99%
“…At the same time, the ecological knowledge and the know-how used to manufacture the relevant tools for hunting are part of the ecological (R i ) and cultural inheritance of these Late Palaeolithic groups. Their ecological footprint and hence the ecological inheritance (R p ) at the landscape scale were still ephemeral at this time, although their ability to modify landscapes may hitherto, as Brown et al (2017) point out, been underestimated.…”
Section: The Beaver As Ecosystem Engineer and Niche Constructormentioning
confidence: 99%
“…Fischer-Kowalski and Haberl, 2007) produces a reductionist and functionalist approach to past human societies based on a false analogy with human metabolism. Alternatively we can consider the development of persistent artificial niches (Laland and O'Brien, 2010;McClure, 2015;Odling-Smee et al, 2013;Brown et al, 2017) which can have selective advantage and so be related to eco-cultural change. If justification for the full integration of archaeological-historical-social evidence with palaeoenvironmental data is still required, we should remember that resilience wains as societies apply notionally optimal management strategies to a landscapes.…”
Section: Framework Of Integration: Degradationism Stability and Susmentioning
confidence: 99%